The Development Strategy Micro, Small, and Medium Enterprise of Bandung City Reviewing from Quality Management - Dedi Mulyasana; Mia Yustika (Almana : Jurnal Manajemen dan Bisnis, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are productive business entities that are the backbone of the country's economy. The Covid-19 pandemic has significantly affected the country's economic sector, based on these circumstances, Indonesia, especially Bandung, needs guidance so that the country's economy can survive this pandemic. MSMEs are implementing various strategies to survive this pandemic, thus this research aims to review these conditions purely due to the impact of the Covid-19 pandemic or related to the business development strategy implemented by MSMEs in the city of Bandung from a quality management perspective. This study used a quantitative research method to see measurable results by collecting data (survey method), with a population of 6,141 fostered MSMEs registered in the city of Bandung and a sample of 80 businesses, using a research instrument in the form of a questionnaire (questionnaire). This research took place in the city of Bandung. Related to this problem, researchers will examine the condition of MSME businesses in terms of quality management. Is the decline in the condition of MSMEs purely due to the impact of the Covid-19 pandemic, or is it related to inappropriate business management.